THE CONTEXT OF THE MALE AGED AND THE LOW ADHERENCE IN PROGRAMS OF PHYSICAL ACTIVITIES TO THE THIRD AGE GROUPS (Fiep Bulletin - online, 2014)
In the width of the theme of age, it is considered relevant to centralize the focus of this study in the male figure, since that the reality in projects of physical activities addressed to the third age is of an essentially female public. from this observation , there was the necessity of understanding the factors that make difficult the adherence of aged men in projects of physical activity, in specific, partners of women who are inserted in the Extensionist Project“ Major Age in Movement“, of the Centro Universitário Feevale, in Novo Hamburgo, RS. The methodological design was characterized in a qualitative, descriptive approach, collecting the information through semi-structured interview and field notes and sorting them out in categories: Occupation of Free Time in the Context of Life of aged people and, Programs of Third age: Perceptions and Suggestions. The collaborators of the survey are aware of the importance of their actions towards the society and some of them are active in social projects as a form of occupying the time. The perceptions related to the programs of third age involving physical activities reveal consciousness of their importance, but not the adherence of this gender matches the literature, that is, lack of time, interest, motivation or stimulus and precarious health, added to the consensus in their answers about the existence of a bigger number of aged women alive than men. So, we reaffirm that the male behavior towards the process of getting old happens form the laziness, acceptation and resignation of these subjects. The information generated from this survey are only the beginning of new reflections to be done about the relation of gender that involves the agedness and the practice of physical activity.
Keywords: physical activity; aging; gender